Global Perspective on the Development of Genetically Modified Immune Cells for Cancer Therapy - Pinte, Laetitia; Cunningham, Amy; Trébéden-Negre, Helene; Nikiforow, Sarah; Ritz, Jerome (Frontiers in Immunology, 2021)
Since the first genetically-engineered clinical trial was posted to clinicaltrials.gov in 2003, chimeric antigen receptor (CAR) and T-cell receptor (TCR) therapies have exhibited unprecedented growth¬. USA, China, and Europe have emerged as major sites of investigation as many new biotechnology and established pharmaceutical companies invest in this rapidly evolving field. Although initial studies focused primarily on CD19 as a target antigen, many novel targets are now being evaluated. Next-generation genetic constructs, starting materials, and manufacturing strategies are also being applied to enhance efficacy and safety and to treat solid tumors as well as hematologic malignancies. Fueled by dramatic clinical efficacy and recent regulatory approvals of CD19-targeted CAR cell therapies, the field of engineered cell therapeutics continues to expand. Here, we review all 744 genetically modified CAR and TCR clinical trials with anticipated accrual of over 28,000 patients posted to clinicaltrials.gov until 31st of December 2019. We analyze anticipated patient enrollment, geographic distribution and phase of studies, target antigens and diseases, current strategies for optimizing efficacy and safety, and trials expected to yield clinical data in the coming 6-12 months.